Urinary tract infections: Virulence factors, resistance to antibiotics, and management of uropathogenic bacteria with medicinal plants: A review - Mbarga Manga Joseph Arsene, Podoprigora Irina Viktorovna, Anyutoulou Kitio Linda Davares, Ngah Esther, Senyagin Alexander Nikolaevich (Journal of Applied Pharmaceutical Science, 2021)
Urinary tract infections (UTIs) are among the most common infections in most countries and they are usually caused by the so-called uropathogenic (UP) microorganisms, including Escherichia coli (80%–90%), Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, Proteus mirabilis, and Klebsiella pneumoniae. Over the years, the growth of resistance to antibiotics has complicated the treatment of UTIs and has direct consequences on the cost of treatment, the severity of infections, and the length of hospitalization. Medicinal plants, used for thousands of years to treat various diseases, constitute a serious alternative to antibiotics in the public health issue of antimicrobial resistance. In this review, the in vitro and in vivo use of medicinal plants and their nanoparticles (silver, gold, zinc, copper oxide, magnesium oxide, iron, etc.) in the management of uropathogens and their virulence factors (VFs) as well as in the management of UTIs themselves have been discussed. Given the advantages offered by the biologically active compounds of medicinal plants as well as their green-synthetized nanoparticles whether used as such or in combination with conventional antibiotics, it can be concluded that herbal medicine can significantly help in the management of UTIs.
Keywords: Urinary tract infections, uropathogens, multidrug resistance, virulence factor antibacterial, phytochemicals, synergy, nanoparticles